ANALISIS PERANAN INTERNAL AUDIT DALAM MEWUJUDKAN PELAKSANAAN GOOD CORPORATE GOVERNANCE PADA PT. BANK TABUNGAN NEGARA, TBK MANADO - Oroh, Ayu Anita Ekaristi; Kalangi, Lintje; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
PT. Bank Tabungan Negara, Tbk Manado is one of the branch offices of BUMN’s, which must implement Good Corporate Governance in accordance with GCG principles set by the Minister of BUMN PER-01 / MBU / 2011. Internal audit is one of the elements in GCG and has a role in overseeing the implementation of corporate management and overseeing any practices undertaken by the company. The implementation of GCG in the bank must follow the rules of BI and follow GCG guidelines by KNKG. Therefore, this study aims to determine the implementation of GCG at the bank and to determine the role of internal audit in realizing the implementation of GCG. This type of research is qualitative descriptive. The method of analysis used in this research is descriptive method with data collection technique such as interview, observation and documentation. The results of this study is Bank Tabungan Negara has implemented GCG according to applicable rules that is by implementing the principles of GCG. Furthermore, internal audit plays a role in realizing the implementation of GCG Bank BTN.Keywords : Analysis, The Role, Internal Audit, Good Corporate Governance, GCG